2017
DOI: 10.4081/cp.2017.999
|View full text |Cite
|
Sign up to set email alerts
|

Glycated Hemoglobin and Red Blood Cell Indices in Non-diabetic Pregnant Women

Abstract: Hemoglobin A1c (HbA1c) is affected by the red blood cell (RBC) lifespan. The association of HbA1c with RBC indices in pregnant women is not widely investigated. In this study, we investigated the association between HbA1c and Hb/RBCs count and RBCs indices; specifically, Hb/RBCs count and indices in non- diabetic pregnant women. Across-sectional study was carried- out at the antenatal care of Saad Abu Elela Hospital, Khartoum, Sudan. Obstetrics history was gathered using questionnaire and body mass index was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
2
5
0
1
Order By: Relevance
“…These ndings suggest that up-regulation of metallothionein gene might be involved in insulin resistance through the modulation of insulin action in type 2 diabetes. Consistently, a previous study showed a signi cant positive correlation between glycohemoglobin (HbA1c) value with Hb, HCT, and MCHC in non-diabetic pregnant women [30].…”
Section: Discussionsupporting
confidence: 84%
“…These ndings suggest that up-regulation of metallothionein gene might be involved in insulin resistance through the modulation of insulin action in type 2 diabetes. Consistently, a previous study showed a signi cant positive correlation between glycohemoglobin (HbA1c) value with Hb, HCT, and MCHC in non-diabetic pregnant women [30].…”
Section: Discussionsupporting
confidence: 84%
“…Intriguingly, data from non-diabetic pregnant women have suggested that there is a positive correlation between HbA1c and haemoglobin, haematocrit and MCHC. 36 Because HbA1c is only tested in seroconverted children in TEDDY, future studies should determine whether this association occurs before or after seroconversion.…”
Section: Discussionmentioning
confidence: 99%
“…This information together with our results of the inverse association between MCV and MCH with HbA1c represents a process that takes place already during an autoimmune attack on the beta cells and may remain until after diagnosis of type 1 diabetes. Intriguingly, data from non‐diabetic pregnant women have suggested that there is a positive correlation between HbA1c and haemoglobin, haematocrit and MCHC 36 …”
Section: Discussionmentioning
confidence: 99%
“…19,20 Also, this finding is contradictory with similar study done by Li et al, among pregnant women and concluded that there was no significant difference of hemogram changes. [21][22] Also, our result showed no clinically significant (≥ 0.05) in RBCs, MCH and MCHC among those women. This finding supported that during pregnancy, the total blood volume increases by about 1.5 L, mainly to supply the demands of the new vascular bed and to compensate for blood loss occurring at delivery.…”
Section: Discussionmentioning
confidence: 47%